Clinical and microbiological characteristics associated with mortality in spontaneous bacterial peritonitis: a multicenter cohort study. - Oliveira, AM (2016)
OBJECTIVES: Spontaneous bacterial peritonitis (SBP) is a prevalent and high mortality complication of cirrhosis. We aimed to describe these patients' clinical and microbiological characteristics and evaluate their impact on outcomes. METHODS: This was a retrospective cohort study including 139 consecutive patients with positive culture SBP from three Portuguese centers diagnosed between 2009 and 2014. Multivariate logistic regression was used to study associations with 30-day mortality. RESULTS: The mean age of the patients was 62 years and 81% of patients were men. The mean model for end-stage liver disease score was 19. Hepatic encephalopathy, hepatorenal syndrome, and variceal bleeding developed in 47, 30, and 21% of patients, respectively. Gram-positive bacteria were isolated in the ascitic fluid of 42% of patients. Resistance to quinolones and multiresistance were found in 33 and 17% of patients, respectively. C-reactive protein level (adjusted odds ratio, 1.16 per 1 mg/l increment) and development of hepatorenal syndrome (adjusted odds ratio, 2.86) were associated independently with 30-day mortality (model's area under the curve, 0.78). CONCLUSION: In this cohort, SBP portended high early mortality. Gram-positive bacteria, bacteria resistant to quinolones, and multiresistant bacteria were identified in considerable proportions of patients. In the setting of the high early mortality and changing microbiological profile, SBP management strategies need to be improved.